Kinetika Kristalisasi Campuran Minyak Sawit Bebas Asam Lemak Trans untuk Produksi Margarin - Ferdinandus Archie Pangestu; Nurheni Sri Palupi; Nur Wulandari; Dimas Supriyadi (Jurnal Teknologi dan Industri Pangan, 2023)
Non-trans-fat (NTF) margarine was produced by substituting partially-hydrogenated palm oil in margarine oil blend with fully-hydrogenated palm oil. Three types of NTF oil blends were used in this study. To obtain an NTF oil blend with similar physical properties to the reference oil blend, which contain partially-hydrogenated oil, the melting properties and crystallization kinetics were evaluated. The iodine value of raw material oil was measured, and the oil was mixed to form the margarine oil blends. Fatty acid composition (FAC) and solid fat content (SFC) of the oil blends were examined. Melting properties of the oil blends were determined based on SFC analysis, while crystallization kinetics were determined using Avrami model. The results showed that there was no trans fatty acids detected in the NTF oil blends. The rate of crystallization constant (k) of the Avrami index of reference oil and NTF-1 oil blend were 0.1413 ± 0.0047 and 0.1369 ± 0.0016 min-n, respectively, whilst their Avrami exponent (n) were 0.93 ± 0.02 and 0.94 ± 0.01, respectively. There was no significant difference on these Avrami indexes, and therefore NTF-1 oil blend could be selected as an alternative oil blend for margarine production.